Penerapan Asuransi Lingkungan Hidup Pada Pemanfaatan Lahan Gambut Di Sektor Kehutanan - Prasetiyo, Hari; Tanjung, Kurnia Togar P.; Jordan, Jeremy (UI Scholars Hub, 2019)
Forest and land fires, especially on peatlands that often occur in Indonesia, have a huge negative impact both for the environment and for the community. The enforcement of civil law to obtain compensation for damages to the environment and the community must be obtained. The basic use of civil liability through absolute responsibility can be made for activities or businesses within a peat ecosystem or have an impact on the peat ecosystem. The basic use of civil liability through strict liability can be made for activities or businesses within a peat ecosystem or have an impact on the peat ecosystem. In practice, however, it is not necessarily that the polluter can fulfill their compensation fully because there are insolvency problems. Environmental insurance can overcome these problems with the risk transfer mechanism. The issuance of PP no. 46 of 2017 on Economic Instruments provides a way for the implementation of environmental insurance in Indonesia. This research is conducted through a normative juridical method by looking at legal materials that have binding legal force such as legislation.